(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In the process of wastewater treatment by coagulation a large amount of sediment is being produced, which is the main drawback of this method. Therefore, the development of utilization or recirculation technology of the waste obtained, the research of the obtained by-products should be conducted. Within the scope of this work, the sediment, that is being formed during the coagulation of the model wastewater containing the wood originated pollutants, was studied. Using the aluminium-containing composition coagulant on a base of polyaluminium chloride, coagulates characterized by the low sludge volume index within 30 minutes (89 ml g-1), and the optimal time of sedimentation is 20-30 minutes. The coagulate particles have an average size of 45.8 μm. The derived coagulate is composed primarily of carbon (27.9%), oxygen (49.4%) and aluminum (10.9%). Carbon, oxygen and hydrogen belong to an organic part of coagulate-the wood pollutants, which, in turn, has a high content of hemicellulose. It is concluded that the existing hemicellulose in the obtained coagulate is characterized by O-acetyl-4-O-methyl-D-glucuron-β-D-xylan with β-(1-4)-glucomannose.